OPTIMALISASI PRODUKSI ASI MELALUI PIJAT OKSITOSIN - Aifa, Wira Eka; Jufenti Ade Fitri; Rifa Yanti; Dilgu Meri (HEALTH CARE: JURNAL KESEHATAN, 2025)
Breast milk is the best food for babies. Breast milk is specifically made for human babies. The nutritional content of breast milk is very special and perfect and meets the needs of infant growth and development. Oxytocin massage is a stimulation to stimulate the release of the hormone oxytocin through oxytocin massage, providing a sense of comfort and instilling confidence in the mother that breast milk will definitely come out and the mother can provide exclusive breastfeeding. This type of research uses a quantitative approach with a one-group pretest-posttest design. This design consists of one group given a pretest before being given treatment, then given treatment and then a posttest to determine the results. The research was conducted in July-August 2025. The sample size was 31 people taken using purposive sampling technique. The results of the study showed that the lowest breast milk production before oxytocin massage was 0 cc while the highest production was 2 cc with an average breast milk production of 0.3 cc. The lowest breast milk production after oxytocin massage was 0 cc while the highest production was 4.3 cc with an average breast milk production of 1 cc. Bivariate test analysis, namely parametric statistical tests using Paired t-test, obtained a p-value < (0.05) which is 0.000 < α = 0.05 which means that oxytocin massage is effective in increasing breast milk production in postpartum mothers. From these results, health services need to implement oxytocin massage as a method to increase breast milk production in postpartum mothers.